Research progress on lightweight design and technology of fiber reinforced plastics components in automobile industry - CHEN Yi-zhe; ZHAO Yue; WANG Hui (Cailiao gongcheng, 2020)
The fiber reinforced plastics (FRP) material is composed of reinforcing fiber and matrix material. It has the characteristics of high strength, low density, good corrosion resistance and strong designability. It has been widely used in the field of automobiles. As the automobiles continue to develop toward low cost, high efficiency, and automation, the manufacturing of composite components faces higher requirements of lightweight. The research progress of lightweight of fiber composite components in automobile field was reviewed from three aspects of materials, structure and forming process. The development and application of continuous fiber composite parts were introduced. The design and forming technology of lightweight composites for FRP in automobile field were given. Prospects and challenges for the development of FRP were presented as well. Under the background of energy saving and emission reduction, fiber composite materials will be widely used in automobile lightweight design.Meanwhile, how to reduce the cost of composite products will become a new challenge.